KAJIAN MEDIA SOSIAL SEBAGAI MEDIA STRATEGIS KOMUNIKASI HUBUNGAN MASYARAKAT DALAM INSTITUSI PEMERINTAH - Arifia S, Maulidha (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2024)
Social media has become an important channel for government institutions to communicate with the public, and the National Narcotics Agency (BNN) is no exception. One social media that is actively used is Instagram. With its large and diverse user base, Instagram offers strategic opportunities for the BNN Public Relations and Protocol Bureau. The purpose of this paper is to analyze the public's reception of BNN's Instagram content and identify effective communication strategies on BNN's Instagram. This paper uses content analysis and reception analysis methods. The results of this analysis are that during 1 month of research from March 2024, there were 66 contents posted. And 19 of them are BNN activities. The content posted by the BNN Instagram account provides clear and complete information but is less interesting and the appearance of the Instagram content page is less organized, so from the results of the research, suggestions are given to make the content display more attractive and tidy up the appearance of the BNN Instagram account page.